The role of cooperation with family in the treatment of adolescent patients with the diagnosis of anorexia nervosa - Bryniarska, Antonina (2024)
Anorexia nervosa (AN) as an eating disorder is characterised by a high mortality rate, severe clinical presentation and increasing prevalence among young patients. The key mechanisms for the course of the illness are denial, minimisation of symptoms and a distorted self-image. These phenomena determine the egosyntonic nature of anorectic symptoms and the associated low motivation for treatment. Therefore, the involvement of underage patients’ parents in the treatment process is crucial. Medical recommendations point to family therapy as the first-choice method for the outpatient treatment of anorexia. Less is known about ways to involve the family in the inpatient treatment process, which is a necessary form of treatment for patients with the most severe clinical picture. The research presented in this thesis explores the importance of building collaboration between professionals and patients' families during the inpatient hospitalisation of a child with a diagnosis of anorexia. The aim was to show both the parents and staff in the process of co-constructing collaboration. To this end, clinical data extracted from a medical record creation programme was used. Due to the nature of the data and research questions, it was decided to use qualitative methods to gain a deeper understanding of the investigated mechanisms: Consensual Qualitative Research and Comparative Case Study. Fro
Keywords: anorexia nervosa; child and adolescent psychiatry; inpatient treatment; cooperation with parents; qualitative research